Human and Technology Collaboration Creates a Smart Society in Lampung Province Area - Tanjung, Tia; Ghazali, Ihwan; Muhida, Riza; Thamrin, Taqwan; Marzuki; Susanty, Wiwin; Wahyuningsih, Dina Ika (ICSIGER- International Conference on Science and Emerging Technology, 2026)
Lampung Province aspires to realize a smart society through collaboration between humans and technology. This study aims to analyze the technology readiness level (TRL) of various ongoing smart society initiatives in Lampung and identify the role of human collaboration in improving this TRL. Research methods include surveys, interviews with technology developers and users, and case studies of several smart society projects in Lampung. The results show that most implemented technologies are still at a low TRL (1-4), namely the basic research and concept validation stage. However, several initiatives have achieved TRL 5-6 (technology validation in a relevant environment), such as agricultural information systems and public transportation applications. Collaboration between academia, industry, and government is crucial to elevate TRL to a higher level (7-9), namely the system demonstration, implementation, and commercialization stages. Policy recommendations focus on increasing research and development (R&D) investment, facilitating technology transfer, and developing an innovation ecosystem that supports improving the TRL of technology for a smart society in Lampung.